Development of Phasmarhabditis hermaphrodita (and members of the Phasmarhabditis genus) as new genetic model nematodes to study the genetic basis of parasitism. Issue 3 (2nd April 2018) - Andrus, P.; Rae, R.
Abstract: The genetic mechanisms of how free-living nematodes evolved into parasites are unknown. Current genetic model nematodes (e.g. Caenorhabditis elegans ) are not well suited to provide the answer, and mammalian parasites are expensive and logistically difficult to maintain. Here we propose the terrestrial gastropod parasite Phasmarhabditis hermaphrodita as a new alternative to study the evolution of parasitism, and outline the methodology of how to keep P. hermaphrodita in the lab for genetic experiments. We show that P. hermaphrodita (and several other Phasmarhabditis species) are easy to isolate and identify from slugs and snails from around the UK. We outline how to make isogenic lines using 'semi-natural' conditions to reduce in-lab evolution, and how to optimize growth using nematode growth media (NGM) agar and naturally isolated bacteria. We show that P. hermaphrodita is amenable to forward genetics and that unc and sma mutants can be generated using formaldehyde mutagenesis. We also detail the procedures needed to carry out genetic crosses. Furthermore, we show natural variation within our Phasmarhabditis collection, with isolates displaying differences in survival when exposed to high temperatures and pH, which facilitates micro and macro evolutionary studies. In summary, we believe that this genetically amenable parasite that shares many attributes with C. elegans as well as being in Clade 5, which contains many animal, plant and arthropod parasites, could be an excellent model to understand the genetic basis of parasitism in the Nematoda.